Biographical fiction a reader - Lackey, Michael (New York Bloomsbury Academic, 2017)
In Biographical Fiction: A Reader, some of the finest scholars and writers of biofiction clarify what led to the rise of this genre, reflect on its nature and form, and specify what it is uniquely capable of doing.
Includes bibliographical references and index.
Keywords: Biographical fiction; Biography as a literary form; Biography in literature; Biographical fiction -- 20th century -- History and criticism